2020
DOI: 10.2147/oarrr.s265806
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of Secukinumab on Patient-Reported Outcomes in the Treatment of Ankylosing Spondylitis: Current Perspectives</p>

Abstract: Ankylosing spondylitis (AS) is a chronic rheumatic disease involving inflammation of the joints and spine, which carries a substantial, lifelong burden for the patient. Secukinumab is a fully human anti-interleukin-17A monoclonal antibody, approved in the USA and EU for the treatment of AS. In this narrative review, we searched PubMed with the aim of consolidating the recent literature regarding the impact of secukinumab on patientreported outcomes in patients with AS. A large clinical trial program has demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…The initial four components are measured on 0-10 cm VAS (Visual analogue score). 12 ASDAS cut-offs for disease activity are <1.3 for remission, <2.1 for low disease activity, ≤3.5 for high disease activity and >3.5 for very high disease activity. 11 BASDAI is a measure of disease activity for ankylosing spondylitis.…”
Section: Methodsmentioning
confidence: 99%
“…The initial four components are measured on 0-10 cm VAS (Visual analogue score). 12 ASDAS cut-offs for disease activity are <1.3 for remission, <2.1 for low disease activity, ≤3.5 for high disease activity and >3.5 for very high disease activity. 11 BASDAI is a measure of disease activity for ankylosing spondylitis.…”
Section: Methodsmentioning
confidence: 99%
“…The chronic inflammation associated with AS, as well as the pain and stiffness in the spine and joints, can contribute to increased fatigue levels. Additionally, the immune system activation and the presence of depression or sleep disturbances can further exacerbate fatigue in AS [79]. The level of fatigue is one of the components used to assess disease activity in the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), which is one of the most commonly used scales in patients with AS.…”
Section: Fatigue In Ankylosing Spondylitismentioning
confidence: 99%
“…In these studies, patients answer surveys that address their pain, fatigue, mood/mental health, general health, sleep, and impact on activities of daily living. Post hoc analysis of secukinumab randomized clinical trials showed that secukinumab improved mental and physical health, as well as their perceived quality of life [ 80 •, 81 83 ]. In addition to their improved quality of life, these patients reported less work absenteeism and increased work productivity [ 81 ].…”
Section: Targeting Il-17 In Ankylosing Spondylitis and Psoriatic Arth...mentioning
confidence: 99%